2016
DOI: 10.1155/2016/7203587
|View full text |Cite
|
Sign up to set email alerts
|

Hib Vaccines: Past, Present, and Future Perspectives

Abstract: Haemophilus influenzae type b (Hib) causes many severe diseases, including epiglottitis, pneumonia, sepsis, and meningitis. In developed countries, the annual incidence of meningitis caused by bacteria is approximately 5–10 cases per population of 100,000. The Hib conjugate vaccine is considered protective and safe. Adjuvants, molecules that can enhance and/or regulate the fundamental immunogenicity of an antigen, comprise a wide range of diverse compounds. While earlier developments of adjuvants created effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 153 publications
(143 reference statements)
0
25
0
3
Order By: Relevance
“…Recently, Naumenko et al [11] reported the structure of the repeating unit of the cell wall O-polysaccharide of the E. albertii O4 strain [11], which is a pentasaccharide comprising of α-linked ᴅ-galactosamine, β-linked ᴅ-glucosamine, β-linked ᴅ-galactose, α-linked ʟ-fucose and α-linked ʟ-rhamnose moieties. In the recent past, several vaccine candidates have been developed to control bacterial infections by conjugating cell wall polysaccharides with suitable proteins, which include vaccines against Haemophilia influenza type b (Hib) [12,13], meningitis [14], pneumococcal infections [15,16] and enteric diseases such as cholera [17], diarrhea [18] and urinary tract infections [19]. Despite the possibility of isolating the polysaccharides by fermentation techniques, it is difficult to get a significant quantity of polysaccharide fragments from natural sources with adequate purity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Naumenko et al [11] reported the structure of the repeating unit of the cell wall O-polysaccharide of the E. albertii O4 strain [11], which is a pentasaccharide comprising of α-linked ᴅ-galactosamine, β-linked ᴅ-glucosamine, β-linked ᴅ-galactose, α-linked ʟ-fucose and α-linked ʟ-rhamnose moieties. In the recent past, several vaccine candidates have been developed to control bacterial infections by conjugating cell wall polysaccharides with suitable proteins, which include vaccines against Haemophilia influenza type b (Hib) [12,13], meningitis [14], pneumococcal infections [15,16] and enteric diseases such as cholera [17], diarrhea [18] and urinary tract infections [19]. Despite the possibility of isolating the polysaccharides by fermentation techniques, it is difficult to get a significant quantity of polysaccharide fragments from natural sources with adequate purity.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) and possesses the highest invasive potential among encapsulated H. influenzae ; thus, it is a major health concern, especially for children. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Haemophilus influenzae type b (Hib) is a widely recognized member of the Haemophilus genus that directly causes respiratory infectious disease with characteristic manifestations of tympanitis, bronchitis and pneumonia in children of all ages, particularly in infants and 1-year-olds [ 1 3 ]. Notably, this pathogen is associated with purulent meningitis in a specific ratio in all Hib-infected patients [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Haemophilus influenzae type b (Hib) is a widely recognized member of the Haemophilus genus that directly causes respiratory infectious disease with characteristic manifestations of tympanitis, bronchitis and pneumonia in children of all ages, particularly in infants and 1-year-olds [ 1 3 ]. Notably, this pathogen is associated with purulent meningitis in a specific ratio in all Hib-infected patients [ 1 , 4 ]. Epidemiological studies of this pathogen have primarily been performed in developed countries and have shown that the incidence in children under the age of 5 in areas such as the US, France, and Switzerland is approximately 20–100/100,000 [ 5 9 ], but few data have been reported for developing areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation